The Global academic research organization network: Data sharing to cure diseases and enable learning health systems. Issue 1 (3rd December 2018) - Fukushima, Masanori; Austin, Christopher; Sato, Norihiro; Maruyama, Tatsuya; Navarro, Eileen; Rocca, Mitra; Demotes, Jacques; Haendel, Melissa; Volchenboum, Samuel L.; Cowperthwaite, Matthew; Silverstein, Jonathan C.; Webb, Chris; et al.
Abstract: Introduction: Global data sharing is essential. This is the premise of the Academic Research Organization (ARO) Council, which was initiated in Japan in 2013 and has since been expanding throughout Asia and into Europe and the United States. The volume of data is growing exponentially, providing not only challenges but also the clear opportunity to understand and treat diseases in ways not previously considered. Harnessing the knowledge within the data in a successful way can provide researchers and clinicians with new ideas for therapies while avoiding repeats of failed experiments. This knowledge transfer from research into clinical care is at the heart of a learning health system. Methods: The ARO Council wishes to form a worldwide complementary system for the benefit of all patients and investigators, catalyzing more efficient and innovative medical research processes. Thus, they have organized Global ARO Network Workshops to bring interested parties together, focusing on the aspects necessary to make such a global effort successful. One such workshop was held in Austin, Texas, in November 2017. Representatives from Japan, Taiwan, Singapore, Europe, and the United States reported on their efforts to encourage data sharing and to use research to inform care through learning health systems. Results: This experience report summarizes presentations and discussions at the Global ARO Network Workshop held in November 2017 in Austin, TX, with representatives from Japan, Korea, Singapore, Taiwan, Europe, and the United States. Themes and recommendations to progress their efforts are explored. Standardization and harmonization are at the heart of these discussions to enable data sharing. In addition, the transformation of clinical research processes through disruptive innovation, while ensuring integrity and ethics, will be key to achieving the ARO Council goal to overcome diseases such that people not only live longer but also are healthier and happier as they age. Conclusions: The achievement of global learning health systems will require further exploration, consensus‐building, funding aligned with incentives for data sharing, standardization, harmonization, and actions that support global interests for the benefit of patients.